2021
DOI: 10.1002/anie.202100185
|View full text |Cite
|
Sign up to set email alerts
|

Transforming a Fluorochrome to an Efficient Photocatalyst for Oxidative Hydroxylation: A Supramolecular Dimerization Strategy Based on Host‐Enhanced Charge Transfer

Abstract: The development of non‐covalent synthetic strategy to fabricate efficient photocatalysts is of great importance in theranostic and organic materials. Herein, a fluorochrome N,N′‐dimethyl 2,5‐bis(4‐pyridinium)thiazolo[5,4‐d]thiazolediiodide (MPT) was transformed into an efficient photocatalyst through supramolecular dimerization in the cavity of cucurbit[8]uril (CB[8]). The host‐enhanced charge transfer interaction within the supramolecular dimer 2MPT‐CB[8] dramatically promoted intersystem crossing to produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 83 publications
1
36
0
Order By: Relevance
“…On the basis of charge recombination mechanism, the enhanced ISC efficiency of G could be attributed to CB [8]enhanced charge transfer interaction. [25,51] The UV-vis absorption spectrum of G showed two absorption peaks at around 260 and 340 nm (Figure 1a), respectively ascribed to naphthalene and methoxyphenyl pyridinium (Figure S16, Supporting Information). Then the original absorption peaks of G almost disappeared and a new absorption peak at 367 nm appeared after G binding with CB [8], suggesting the formation of CB [8]mediated ICT assembly.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of charge recombination mechanism, the enhanced ISC efficiency of G could be attributed to CB [8]enhanced charge transfer interaction. [25,51] The UV-vis absorption spectrum of G showed two absorption peaks at around 260 and 340 nm (Figure 1a), respectively ascribed to naphthalene and methoxyphenyl pyridinium (Figure S16, Supporting Information). Then the original absorption peaks of G almost disappeared and a new absorption peak at 367 nm appeared after G binding with CB [8], suggesting the formation of CB [8]mediated ICT assembly.…”
Section: Resultsmentioning
confidence: 99%
“…If a dimer is sustained with strong restriction, as will be introduced later, its pseudostatic excited state can remain as a dimeric form before relaxation to the ground state. On account of the restriction, the relaxation will mainly choose a radiative pathway of high efficiency, which could lead to dimerization-induced enhanced emission (DIEE) , or room-temperature phosphorescence (RTP). , If a dimer is dynamically and loosely held with weak restriction, its excited dimer may have more chances to dissociate into an excited monomer, which then behaves as a supramolecular catalyst to trigger subsequent reactions. , Similar profiles could also be found for the redox products of noncovalent dimers, working either as stable near-infrared (NIR) probes or catalytic supramolecular radicals depending on oxygen content. , …”
Section: Introductionmentioning
confidence: 92%
“…Zhang et al reported a supramolecular dimerization of two MPT 2+ guests with one CB[8], yielding a 2MPT 2+ -CB­[8] dimer with two guests arranged in a parallel and staggered conformation (Figure ). Owing to their acceptor–donor–acceptor structures, two MPT 2+ guests were coupled with each other as a discrete charge-transfer (CT) pair inside cavity. Upon excitation, the CT interaction was known to promote the intersystem crossing process and generated triplets through a charge separation and recombination mechanism. ,, The supramolecular CT dimer of 2MPT 2+ -CB­[8] thereby behaved as a triplet generator, displaying an increasing yield of triplets upon photoexcitation.…”
Section: Supramolecular Dimerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CB [8] is a relatively large homologue within the CB[n] family. It can bind [76,77] simultaneously two fluorescent molecules inside its cavity as J-aggregates, leading to a red-shifted emission of the guests. Ma and co-workers [78] have synthesized a color-tunable host-guest complex, which is composed of thiazolothiazole methyl viologen (TMV 2+ ) guests and CB [8].…”
Section: Cucurbit[n]urilsmentioning
confidence: 99%